Adhesive material, method for producing adhesive material, method of use of adhesive material

By introducing light-responsive azo compounds into the polymer and adjusting the bonding intensity with ultraviolet light, the existing light-responsive materials are solved for complex operation and not suitable for water environments, and convenient bonding and disengagement are achieved, and adhesive properties are maintained in water environments.

JP2025056919APending Publication Date: 2025-04-09NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023166453
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing light-responsive materials need to be repeatedly irradiated under different wavelengths of light, which is complex and time-consuming, and is not suitable in water environments, and it is easy to leave sticky marks during use, limiting its application range.

Method used

Using a polymer containing a light-responsive azo compound, the bonding intensity is changed by changing the structure of the azo compound and ultraviolet light irradiation, thereby achieving convenience of bonding and disengagement, and maintaining bonding performance in a water environment.

Benefits of technology

Reused light-responsive adhesives are realized in air and water environments, simplifying the bonding and disengagement process, avoiding the retention of adhesive marks, and expanding the scope of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056919000001_ABST
    Figure 2025056919000001_ABST
Patent Text Reader

Abstract

To provide a photo-responsible adhesive material capable of simply and easily adhering with and detaching from a target, and capable of using under a broad environment, a producing method thereof and use method thereof.SOLUTION: An adhesive material includes a copolymer of a compound represented by the formula (1) for dodecyl glycerol itaconate and a photoresponsive azo compound represented by formula (2) (where m is an integer selected from 10 to 14), and the adhesive strength changes with the presence or absence of ultraviolet light exposure, and, the adhesive strength decreases when exposed to ultraviolet light and returns to its original state without other light exposure when not exposed to ultraviolet light.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive material that can be repeatedly used in an air environment or underwater, and in particular to an adhesive material from which an adhered substance can be easily removed by irradiation with ultraviolet light, as well as a method for producing such an adhesive material and a method for using such an adhesive material. [Background technology]

[0002] Photochromic compounds such as azobenzene and spirooxazine are known as materials that respond to light irradiation. These photoresponsive materials are expected to be used in actuators, adhesives, and the like (Non-Patent Documents 1-3, Patent Documents 1-2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6938063 [Patent Document 2] Patent No. 7012392 [Non-patent literature]

[0004] [Non-Patent Document 1] Youfeng Yue et al. “Light-induced mechanical response in crosslinked liquid-crystalline polymers with photoswitchable glass transition temperatures”, Nature Communications, 2018, 9, 3234 [Non-Patent Document 2] Ruiyang Zhao et al. “Smart responsive azo-copolymer with photoliquefaction for switchable adhesive application”, ACS Appl. Mater. Interfaces 2022, 14, 16678 [Non-Patent Document 3] Shotaro Ito et al. “Light-induced reworkable adhesives based on ABA-type triblock copolymers with azopolymer termini”, ACS Appl. Mater. Interfaces 2018, 10, 38, 32649 Summary of the Invention [Problem to be solved by the invention]

[0005] The photoresponsive materials described in the above Patent Documents 1-2 and Non-Patent Documents 1-3 undergo a state change between solid and liquid or between hard and soft by repeated irradiation with ultraviolet light and visible light. In the case of such photoresponsive materials, it is necessary to irradiate two types of light with different wavelengths in order to cause a state change, which makes the operation complicated and takes time for irradiation. Furthermore, since the photoresponsive materials become liquid when irradiated with ultraviolet light, when they are used for adhesion, there are problems such as the photoresponsive material remaining on the object to be adhered leaving adhesion marks, and the material cannot be used underwater, and the range of application is limited.

[0006] In particular, when various components such as semiconductor components and optical components, medical materials, and the like are adhered to objects for storage or transportation, it is desirable to have a material that can be adhered simply and easily and removed cleanly. The present invention has been made to solve such problems, and aims to provide a light-responsive adhesive material that can adhere to objects simply and easily and remove them, and that can be used in a wide range of environments. Another aim is to provide a method for producing and using such an adhesive material. [Means for solving the problem]

[0007] The present inventors have discovered a compound represented by the following formula (1): [ka] By using an adhesive material containing a copolymer with a photoresponsive azo compound represented by the following formula (2), [ka] (In formula (2), m is selected from an integer of 10 to 14.) The inventors have found that the adhesive strength changes depending only on the presence or absence of ultraviolet light irradiation, and that this allows objects to be easily adhered to each other and easily detached by ultraviolet light irradiation, and have thus completed the present invention. Specifically, the following adhesive material is provided. In this specification, adhesion simply means that objects are stuck to each other, and is a concept that includes adhesion.

[0008] Specifically, the following adhesive materials are provided: (1) dodecyl glyceryl itaconate represented by the following formula (1), [ka] It contains a copolymer with a photoresponsive azo compound represented by the following formula (2), [ka] (In formula (2), m is selected from an integer of 10 to 14.) The adhesive strength changes depending on the presence or absence of ultraviolet light irradiation, and decreases when irradiated with ultraviolet light, and returns to its original strength when not irradiated with ultraviolet light without being irradiated with any other light. (2) The adhesive material according to (1) above, wherein the photoresponsive azo compound has a liquid crystal phase. (3) The adhesive material according to (1) or (2), wherein the weight ratio of the photoresponsive azo compound to the dodecylglyceryl itaconate is 50% or less. (4) The adhesive according to (1) or (2), wherein the elastic modulus of the adhesive is lower when irradiated with ultraviolet light than when not irradiated with ultraviolet light, and the elastic modulus changes by 8-22 MPa between when irradiated with ultraviolet light and when not irradiated with ultraviolet light. (5) The adhesive according to (3) above, in which the elastic modulus of the adhesive is lower when irradiated with ultraviolet light than when not irradiated with ultraviolet light, and changes by 8-22 MPa between when irradiated with ultraviolet light and when not irradiated with ultraviolet light. (6) The adhesive material according to (1) or (2) above, which is used underwater. (7) The adhesive according to (3) above, which is used underwater. (8) The adhesive according to (4) above, which is used underwater.

[0009] Also provided are the following methods for producing and using the adhesive material. (9) A method for producing the adhesive material according to (1) or (2), comprising the steps of: Dodecyl glyceryl itaconate represented by the following formula (1), [ka] A photoresponsive azo compound represented by the following formula (2): [ka] (In formula (2), m is selected from an integer of 10 to 14.) A method for producing an adhesive material, comprising copolymerizing (10) The method for producing an adhesive material according to (9) above, wherein the weight ratio of the photoresponsive azo compound to the dodecylglyceryl itaconate is 50% or less. (11) A method for using the adhesive according to (1) or (2) above, comprising adhering an object to the adhesive for storage or transportation. (12) A method for using the adhesive according to (4) above, comprising adhering an object to the adhesive for storage or transportation. (13) A method for using the adhesive according to (6) above, comprising adhering an object to the adhesive, and then storing or transporting the adhesive in water. (14) A method for using the adhesive according to (8) above, comprising adhering an object to the adhesive, and then storing or transporting the adhesive in water. Effect of the Invention

[0010] According to the present invention, it is possible to provide a light-responsive adhesive material that can be simply and easily attached to an object and cleanly detached, and that can be used in a wide range of environments. It is also possible to provide a method for producing and using such an adhesive material. [Brief description of the drawings]

[0011] [Figure 1] 1 shows differential scanning calorimetry (DSC) data for azo compounds. [Diagram 2] 5A to 5C are schematic diagrams illustrating changes in an adhesive material caused by irradiation with ultraviolet light. [Diagram 3] FIG. 2 is a diagram showing a structural change of an azo compound due to irradiation with ultraviolet light. [Figure 4] 2A to 2C are diagrams illustrating examples of polymer chemical structures of the adhesive material of the present embodiment. [Diagram 5] FIG. 1 is a schematic diagram showing adhesion and detachment of objects. [Figure 6] FIG. 1 is an explanatory diagram of a probe tack test. [Figure 7] 1 is a graph showing the relationship between time and force for a probe tack test. [Figure 8] 1 is a graph showing adhesion before and after irradiation with ultraviolet light. [Figure 9] 1 is a micrograph of the film produced. [Figure 10] These are photographs of a polystyrene ball adhered to a film (Figure 10(A) before exposure to UV light) and of the ball detached from the film by exposure to UV light (Figure 10(B) after exposure to UV light). [Figure 11] The photographs show each object adhered to the film. [Figure 12] This is a photograph of the adhesive used underwater. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiments of the present invention will be described in detail. In the embodiments of the present invention, when a temperature range, a concentration range, etc. are indicated, the upper limit and the lower limit are included unless otherwise specified. In addition, the percentage concentration indicates mass %.

[0013] The adhesive material of the present embodiment comprises dodecyl glyceryl isopropyl acetate represented by the following formula (1), [ka] It is characterized by containing a copolymer with a photoresponsive azo compound (sometimes simply referred to as an azo compound) represented by the following formula (2). [ka] This copolymer contains a dodecyl glyceryl itaconate-based repeating unit represented by the following formula (3) and an azo compound-based repeating unit represented by the following formula (4). [ka] [ka] (In formulas (2) and (4), m is an integer of 10 to 14.)

[0014] Dodecyl glyceryl itaconate (1-(2,3-dihydroxypropyl) 4-dodecyl itaconate, DGI) has been used as a main component in polymer film structures, and azo compounds have been used as photoresponsive components and crosslinkers in films.

[0015] Here, azo compounds with m of 10-14 (the number of carbon atoms between O(oxygen)-O(oxygen) is 12-16) have characteristic properties in that they are liquid crystal monomers. Figure 1 shows DSC data for an azo compound represented by the above formula (2) with m of 4 (Figure 1(A), carbon number 6, C6-azo) and an azo compound with m of 10 (Figure 1(B), carbon number 12, C12-azo). The data in Figure 1(A) is shown in Figure 7(b) of Patent Document 1, and the data in Figure 1(B) is the measurement data for C12-azo (m=10) described later. Measurements were performed under dark conditions with a temperature rise and fall rate of 2°C / min using a DSC measurement device (SII Nano Technology Co., Ltd., product number 6100). This DSC is differential scanning calorimetry, one of the most commonly used measurement methods in thermal analysis, and measures changes in enthalpy (calorie) and specific heat capacity. The vertical axis of the graph shows "heat flow," which is the amount of energy that flows in and out per unit time. DSC data is also a useful measurement method for studying phase transitions in liquid crystals. It is used to measure the heat supplied and discharged during processes such as phase transitions.

[0016] Specifically, in FIG. 1(A), the endothermic peak seen near 65°C indicates endothermic heat caused by "melting" from crystals. Also, an exothermic peak is seen near 29°C, which indicates heat generation due to "crystallization". Meanwhile, in the DSC data in FIG. 1(B), multiple peaks (39, 60, 61°C) are seen. The first endothermic peak (39°C) indicates endothermic heat caused by the phase transition from the crystal phase to the liquid crystal phase, and the second endothermic peak (61°C) indicates endothermic heat caused by the phase transition from the liquid crystal phase to the isotropic liquid phase. Also, the exothermic peak near 60°C indicates heat generation caused by the isotropic liquid phase to the liquid crystal phase. Since there is no exothermic peak caused by the phase change from the liquid crystal phase to the crystal phase in FIG. 1(B), the heated liquid crystal phase can stably maintain the liquid crystal state even at room temperature (25°C). Such liquid crystal monomers have a significant effect on the mechanical properties of polymer materials (e.g., softer properties than polymers synthesized from non-liquid crystal monomers). Thus, the crystal and the liquid crystal monomer have different DSC data, and the liquid crystal monomer has both the fluidity of a liquid and the regularity of a crystal. In other words, it can be said to have a soft property. And since the DGI monomer is also a liquid crystal monomer, the adhesive material according to this embodiment has a property of clearly expressing liquid crystallinity, unlike conventional photoresponsive materials, in that both the azo compound and the DGI are liquid crystal monomers and are formed from both liquid crystal monomers. The azo compound moiety exhibits liquid crystallinity when m=10 or more, but the synthesis yield decreases as the value of m increases. From the viewpoint of industrial production, it is preferable to use an azo compound monomer with m=10-14.

[0017] Then, by using DGI monomer and azo compound monomer with m of 10-14 as raw materials, and heating and polymerizing them in the presence of a polymerization initiator, a copolymer polymer containing dodecyl glyceryl itaconate repeating units represented by the above formula (3) and photoresponsive azo compound repeating units represented by the above formula (4) can be obtained. This polymer is the main component of the adhesive and the photoresponsive active ingredient. This polymer synthesized using liquid crystal azo compound monomer with m of 10-14 as raw material is softer than one using non-liquid crystal monomer (m=4). Therefore, local shape changes due to light are likely to occur. In addition, ultraviolet light can easily cause changes in the elastic modulus of polymers (for example, films), which is closely related to the adhesive strength of the film. Furthermore, crosslinked polymers can be released more cleanly than non-crosslinked polymers. Therefore, adhesion and release are possible just with or without irradiation of ultraviolet light. In addition, no adhesive remains on the object to be adhered, leaving no traces. Furthermore, this adhesive maintains its adhesive strength even underwater, and since ultraviolet light can penetrate water, it can also be used underwater.

[0018] The polymerization initiator used in polymerizing these monomers is not limited, but examples thereof include azo-based polymerization initiators such as 1,1'-azobis-(cyclohexane-1-carbonitrile) and 1,1'-azobis-(isobutyronitrile), peroxides such as benzoyl peroxide and lauroyl peroxide, acylphosphine oxide-based polymerization initiators, and alkylphenone-based polymerization initiators. These can be used alone or in combination of two or more. The amount of the polymerization initiator used is usually 0.05-3.0% by mass, preferably 0.1-2.0% by mass, based on the total amount of the DGI monomer and the azo compound monomer. The heating temperature during the polymerization reaction is 100-130°C, preferably 110-120°C. Furthermore, it is preferable to add an organic solvent, since the viscosity can be reduced and the reaction can be accelerated. The organic solvent may be a common organic solvent, and is not particularly limited. Examples of the organic solvent include aromatic hydrocarbon solvents such as toluene and xylene, and ether solvents such as 1,4-dioxane and cyclopentyl methyl ether.

[0019] The adhesive of the present embodiment can also be used as an adhesive containing other polymers and various additives within a range that does not significantly impair adhesion or releasability (for example, 60% by mass or less, preferably 50% by mass or less, more preferably 40% by mass or less, based on the total amount of the DGI monomer and the azo compound monomer). Examples of other polymers include, but are not limited to, acrylic polymers, silicone polymers, and urethane polymers. Examples of additives include, but are not limited to, fillers, reinforcing agents, and functional additives.

[0020] The adhesive material of this embodiment contains the above-mentioned polymer, specifically an azo compound, as an active ingredient, has adhesiveness under normal light conditions, whether indoors or outdoors, and its adhesive strength changes when exposed to ultraviolet light (ultraviolet rays 280-380 nm, for example 365 nm). Although ultraviolet light is present in small amounts under normal light conditions such as sunlight and indoor light, it can reach 50-100 W / cm when exposed to UV light, etc. 2 By shining light at a pinpoint intensity of 100 or more, the adhesive strength can be changed. That is, the change in adhesive strength of this adhesive material is caused by the presence of the azo compound of this embodiment. The adhesive strength of this adhesive material decreases when irradiated with ultraviolet light, but when the irradiation of ultraviolet light is stopped, the adhesive strength returns to its original state without irradiation with light of a specific wavelength. In other words, the adhesive material naturally recovers. For example, under various light environments such as natural light, sunlight, indoor light (when normal lighting is on or off), and a darkroom, the adhesive strength of the adhesive material can be repeatedly reduced and restored depending on whether or not it is irradiated with ultraviolet light.

[0021] As mentioned above, there is a difference in the properties between the azo compound C12-azo and the azo compound C6-azo. The properties of the polymer materials synthesized as monomers of these azo compounds are also different. In particular, the elastic modulus of the polymer material made of the liquid crystal monomer (C12-azo) is lowered. Patent Document 1 describes that a polymer material (film) which is a polymer compound of C6-azo and DGI monomer undergoes a curved or bent shape change as a whole when irradiated with ultraviolet light, but in the polymer material made of C12-azo and DGI monomer, a localized uneven shape change occurs. This uneven shape change causes the movement of the polymer chain in the ultraviolet light irradiated part. Patent Document 1 describes that the glass transition temperature (Tg) of the polymer material in the ultraviolet light irradiated part decreases, and the glass transition temperature affects the adhesive force. When the glass transition temperature decreases, the elastic modulus of the polymer material also decreases further. Therefore, when the ultraviolet light irradiation is stopped, the adhesive material containing the azo compound (C12-azo) as an active ingredient easily returns to its original shape, and the adhesive force also returns without other light irradiation. In other words, the adhesive strength is restored without pinpoint irradiation with visible light or the like after irradiation with ultraviolet light. As described above, the polymer material of C6-azo and DGI monomer has a high elastic modulus and is thought to have no localized changes in uneven shape, and can be said to have completely different properties from the polymer material of C12-azo and DGI monomer in this embodiment.

[0022] FIG. 2 shows a schematic diagram explaining the change in the adhesive caused by ultraviolet light irradiation. FIG. 3 shows the structural change of the azo compound (in this example, an azo compound with m=10) at that time. The DGI monomer 1 has a cross-linked polymer structure 5 (polymer chain), and the adhesive 7 forms a polymer structure in which the azo compound monomer 3 is bonded between the DGI monomers 1 arranged in layers. When the polymer has such an ordered structure, the azo compound, which is a photoresponsive functional molecule, amplifies the collective molecular motion in the ordered structure. That is, when ultraviolet light is irradiated, the azo compound is isomerizes from a trans form to a cis form, changing the structure of the compound, and this change in structure also changes the shape of the adhesive as shown in FIG. 2, causing a local shape change and decreasing the adhesive force. Here, when the irradiation of ultraviolet light is stopped, the adhesive instantly returns to its original state, that is, the adhesive force also returns. In this way, when the azo compound is in the trans form, the adhesive force is strong, and it is possible to easily adhere an object by pressing it against the adhesive, and to transport the object while maintaining that state. Here, the larger the contact area between the object and the adhesive, the stronger the adhesive strength. On the other hand, when the azo compound is a cis form, the adhesive strength is weakened by the above-mentioned shape change, and the object is detached. As a result, the adhesive of this embodiment can simply and easily adhere and detach objects.

[0023] Examples of objects to be adhered to the adhesive include various parts and members such as semiconductor parts, electrical equipment parts, precision optical parts, and medical parts. There is no limitation on the type, shape, and size of the material of the object, but examples include wood, metal, plastic, rubber, stone, and glass, and various materials such as polystyrene, polypropylene, silicon wafers, and fluororubber. These may be different materials, such as hard and soft. In addition, adhesion to and detachment from these flat, spherical, and convex surfaces are also possible. In addition to these objects, biological samples can also be used.

[0024] Moreover, it is preferable that the elastic modulus of the adhesive varies between 8-22 MPa. If the elastic modulus is large, the adhesive itself tends to become hard and has poor adhesion, whereas if the elastic modulus is small, the adhesive itself becomes too soft and the shape change during irradiation with ultraviolet light is poor. Non-Patent Document 1 describes that the Young's modulus (elastic modulus) of the copolymer of the azo compound with m being 4 and DGI, which is represented by the above formula (2), is 65.6-140 MPa. Although such copolymer polymer compounds with a large elastic modulus tend to become hard, the adhesive according to the present embodiment has a small elastic modulus and is relatively soft, so it is very suitable as an adhesive. The elastic modulus is preferably about 10-22 MPa when not irradiated with ultraviolet light, and about 8-18 MPa when irradiated with ultraviolet light. The shape change of this adhesive depends on the structural change of the photoresponsive azo compound, and the elastic modulus can be adjusted by changing the weight ratio of DGI and azo compound. As mentioned above, an azo compound with m of 10-14 has a soft property, while a large weight ratio of the azo compound to the DGI increases the crosslink density of the polymer, making the adhesive itself more likely to harden and increasing the elastic modulus. Therefore, the weight ratio of the azo compound to the DGI (azo compound / DGI) is preferably 50% or less, more preferably 40% or less. On the other hand, the azo compound may be contained in an amount of about 2-4% relative to the DGI, but from the viewpoint of adhesive strength and releasability, the azo compound / DGI is preferably 11% or more, more preferably 17% or more. If the adhesive does not contain various additives, the weight of the entire adhesive is almost the total weight of the DGI and the azo compound. In this way, the optimal elastic modulus can be achieved by changing the weight ratio of the DGI and the azo compound.

[0025] The adhesive may be in the form of a film, sheet, plate, rod, etc., and localized changes in shape occur when irradiated with ultraviolet light, reducing the contact area between the adhesive and the object to be adhered, lowering the adhesive strength and allowing the object to be easily detached. Although the chemical structure of the polymer of this embodiment is difficult to express as a general formula, when the azo compound monomer of this embodiment and the DGI monomer are copolymerized, for example, when the azo compound monomer with m=10 (the number of carbon atoms between OO is 12) (FIG. 3) is used, it is considered to have a polymer chemical structure as shown in FIG. 4.

[0026] Fig. 5 shows a schematic diagram illustrating the adhesion and detachment of objects. Fig. 5(A) shows the case where there is one object, and Fig. 5(B) shows the case where there are two objects. Under indoor lighting conditions, a film, which is an adhesive material 7, is attached to a glass substrate 11, and an object 15 is pressed against the film by hand to adhere it. Then, when ultraviolet light is irradiated from above (backside) the adhesive material 7 toward the adhesive surface 7a, the adhesive strength decreases, and the object 15 is detached from the adhesive surface 7a. When the irradiation of ultraviolet light is stopped, the adhesive strength returns to normal without being affected by irradiation of light of a specific wavelength, so that the object can be used repeatedly. Also, as shown in FIG. 5(B), when there are multiple objects, by changing the irradiation position of the ultraviolet light, the adhesive strength changes only in the part where the light hits the pinpoint, and each object 15, 17 can be selectively detached by providing a time difference between them.

[0027] From the above, according to this embodiment, an adhesive material having dynamic adhesive performance can be produced by changing the shape with or without ultraviolet light irradiation. This adhesive material can reversibly adhere to flat, spherical, and convex surfaces of different materials such as hard and soft without leaving any residual or adhesive marks. In addition, since the adhesive material of this embodiment does not become liquid when irradiated with ultraviolet light, it can adhere not only under normal air conditions but also under high humidity environmental conditions such as underwater. Furthermore, since the adhesive strength of this adhesive material differs depending on whether or not it is irradiated with ultraviolet light, it is possible to carry objects to be adhered (e.g., plates, balls, etc.) with different volumes and weights, and to drop balls, etc. only by irradiating them with ultraviolet light, which is a specific type of light. Furthermore, it is possible to use it continuously (adhere-carry-peel) using only one type of light, ultraviolet light, without irradiating other light, and without waiting time for recovery of adhesiveness. For example, it is also possible to produce a liquid crystal polymer film as an adhesive material. Next, the present invention will be described in more detail with reference to examples, but the scope of the present invention is not limited to the following examples. EXAMPLES

[0028] (Experimental Example 1) (Synthesis of DGI Monomer) According to the synthesis procedure shown in the chemical reaction formula below, 1-(2,3-dihydroxypropyl)4-dodecyl itaconate (dodecylglyceryl itaconate, DGI, formula (1)) was synthesized based on the following references A and B. Reference A: K. Naitoh, Y. Ishii, K. Tsujii, J. Phys. Chem. 1991, 95, pp7915-7918. Reference B: K. Tsujii, M. Hayakawa, T. Onda, T. Tanaka, Macromolecules 1997, 30, pp7397-7402. [ka]

[0029] Itaconic anhydride (25.0 g, Sigma-Aldrich) and 1-dodecanol (40.0 g, Tokyo Chemical Industry Co., Ltd.) were stirred at 110°C for 1 h. The mixture was then cooled to room temperature, and 80 ml of hexane was added while vigorously stirring to precipitate a white solid. The solid was then filtered and recrystallized with ethanol (Fujifilm Wako Pure Chemical Industries Co., Ltd.) to obtain dodecyl itaconate, an intermediate. Dodecyl itaconate (5.0 g) was dissolved in 5 ml of toluene, and glycidol (3.75 g) (Tokyo Chemical Industry Co., Ltd.) and pyridinium p-toluenesulfonate (10 μg, Tokyo Chemical Industry Co., Ltd.), a catalyst, were added, and the mixture was stirred at 100°C for 5 hours. After cooling, the solvent was distilled off, and the resulting crude product was purified by silica gel (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) column chromatography using a mixture of ethyl acetate:hexane = 3:2 as the developing solvent, and then recrystallized with a mixture of acetone:hexane = 1:1 to obtain DGI. Note that in the following experimental examples, the same reagents were used for the common compounds. Also, the preparation of DGI 1 HNMR spectrum and 13For the CNMR measurement, a sample was prepared by the following method, and a nuclear magnetic resonance apparatus (Bruker Advance NMR, product number) was used under the following measurement conditions. In the following experimental examples, spectrum measurements were also performed using the same apparatus and under the same operation and conditions. Preparation method: The synthesized compound was completely dissolved in a deuterated solvent and placed in an NMR sample tube so that the solution was 4-5 cm high from the bottom. The liquid volume was about 0.6 mL. Measurement conditions: Measurement was performed automatically using an Advance NMR spectrometer manufactured by Bruker. 1 In the case of 1 H NMR, the concentration was 1 wt % and the measurement was performed for 5 minutes. 13 In the case of C NMR, the concentration was about 5-10 wt % and the measurement was performed for about 1 hour.

[0030] 1 H NMR (400 MHz, DMSO-d6) δ 6.24(s, 1H), 5.83 (s, 1H), 4.93 (d, J=5.16 Hz, 1H), 4.66 (t, J1=11.24 Hz, J2=5.64 Hz, 1H), 4.12 (dd, J1=11.12 Hz, J2=4.32 Hz, 1H), 3.95-4.02 (m, 3H), 3.67 (m, 1H), 3.36 (m, 2H), 1.54 (m, 2H), 1.25 (m, 18H), 0.86 (t, 3H); 13 C NMR (100 MHz, DMSO-d6) δ 171.16, 166.53, 134.88, 129.53, 70.09, 67.04, 65.09, 63.39, 37.98, 32. 17, 29.91, 29.88, 29.83, 29.80, 29.58, 29.49, 28.92, 26.16, 22.97, 14.82.

[0031] (Experimental Example 2) (Synthesis of azo compound monomer 1) Synthesis of C12-azo(m=10) (1) Experimental Example 2-1: Synthesis of C12-azo intermediate (formula (5)) [ka] 50 ml of 2.4 mol / L hydrochloric acid (Fujifilm Wako Pure Chemical Industries, Ltd.) was added to 4-aminophenol (4.36 g, 40 mmol, Tokyo Chemical Industry Co., Ltd.), and then a solution of sodium nitrite (3.32 g, 48 mmol, Fujifilm Wako Pure Chemical Industries, Ltd.) dissolved in 4 ml of distilled water was added dropwise while cooling and stirring at -3°C, and stirring was continued at 0°C for 30 minutes. When this solution was added dropwise to a mixed solution of o-cresol (4.32 g, 40 mmol, Tokyo Chemical Industry Co., Ltd.) and 16 ml of 20% aqueous sodium hydroxide (Tokyo Chemical Industry Co., Ltd.) at -3°C, a yellow precipitate was formed. This mixture was shielded from light with aluminum foil and stirred at room temperature for 22 hours. The mixed solution was acidified with hydrochloric acid (2.4 mol / l) while cooling, and the precipitated brown precipitate was filtered, and the obtained solid was washed with water and dried at room temperature. The black solid thus obtained was then purified by silica gel column chromatography using a mixture of ethyl acetate and hexane (1:2) as a developing solvent, and recrystallized from a mixture of acetone and hexane to obtain a yellow solid (formula (5)).

[0032] 1 H NMR (400 MHz, DMSO-d6) δ 10.08 (s, 1H), 10.04 (s, 1H), 7.70 (dd, J1 = 6.8 Hz, J2 = 1.9 Hz, 2H), 7.60 (d, J= 2.0 Hz, 1H), 7.55 (dd, J1 = 8.4 Hz, J2 = 2.4 Hz, 1H), 6.92 (d, J = 8.4 Hz, 1H), 6.90 (dd, J1 =6.8 Hz, J2 = 1.9 Hz, 2H), 2.20 (s, 3H); 13 C NMR (125MHz, DMSO-d6) δ 160.1, 158.4, 145.5, 145.3, 125.1, 124.3, 122.6, 116.0, 115.1, 16.2.

[0033] (2) Experimental Example 2-2: Synthesis of C12-azo intermediate (formula (6), m = 10) [ka] 4,4'-Dihydroxy-3-methylbenzene (formula (5), 0.767g, 3.36 mmol), 12-bromo-1-hexadecanol (2.38g, 8.4 mmol, Tokyo Chemical Industry Co., Ltd.), potassium carbonate (1.39g, 10.08 mmol, Fuji Film Wako Pure Chemical Co., Ltd.), and potassium iodide (33mg, 0.20mmol, Tokyo Chemical Industry Co., Ltd.) were added with 20ml of N,N-dimethylformamide (DMF, Fuji Film Wako Pure Chemical Co., Ltd.). This mixture was stirred at 120°C for 72 hours, and then water was added to precipitate the product. The precipitate was then filtered and recrystallized with ethanol (Fuji Film Wako Pure Chemical Co., Ltd.) to obtain a yellow powder (6) (C12-azo intermediate, m=10).

[0034] 1 H NMR (500 MHz, CDCl3) δ7.85 (d, J = 8.9, 2 H), 7.71-7.74 (m, 2 H), 6.98 (d, J = 9.0, 2 H), 6.90 (d, J = 9.3, 1 H), 4.01-4.06 (m, 4 H), 3.64 (t, J = 6.7, 4 H), 2.29 (s, 3 H), 1.78-1.86 (m, 4 H), 1.54-1.59 (m, 4 H), 1.44-1.52 (m, 4 H), 1.26-1.40 (m, 36 H); 13 C NMR (100 MHz, CDCl3) δ161.04, 159.45, 146.99, 146.37, 127.51, 124.19, 123. 45, 123.38, 114. 64, 110.51, 68.31, 68.25, 63.10, 32. 81, 29.66, 29.60, 29.44, 29.39, 29.25, 29.22, 26.11, 26.02, 25.74, 16.41

[0035] (3) Experimental Example 2-3: Synthesis of azo compound C12-azo (formula (7), m = 10) [ka] Azo compound monomer intermediate (formula (6), m = 10) (0.554g, 0.93 mmol) was dissolved in 20 ml of dehydrated tetrahydrofuran (THF, Fujifilm Wako Pure Chemical Industries, Ltd.), triethylamine (0.23g, 2.4 mmol, Tokyo Chemical Industry Co., Ltd.) was added, and the solution was cooled to 0 ° C. Then, a solution of methacryloyl chloride (0.39g, 3.7 mmol, Tokyo Chemical Industry Co., Ltd.) in dehydrated THF (10 mL, Fujifilm Wako Pure Chemical Industries, Ltd.) was slowly added dropwise with a syringe. After the dropwise addition, the mixture was stirred at 0 ° C. for 10 minutes, and then stirred at room temperature for 24 hours. After the reaction, the solvent was distilled off under reduced pressure, and dichloromethane and 0.1 mol / l HCl aqueous solution were added to the residue and separated, and the organic layer was dried with anhydrous magnesium sulfate (Fujifilm Wako Pure Chemical Industries, Ltd.), and the solvent was distilled off under reduced pressure. The resulting residue was purified by silica gel column chromatography (ethyl acetate:hexane=1:10) to obtain the desired azo compound monomer (7) (m=10).

[0036] 1 H NMR (500 MHz, CDCl3) δ7.85 (d, J = 9.1, 2 H), 7.62-7.65 (m, 2 H), 6.98 (d, J = 9.0, 2 H), 6.90 (d, J = 9.5, 1 H), 6.10 (bs, 2 H), 5.54 (bs, 2 H), 4.14 (t, J = 6.7, 4 H), 4.01-4.06 (m, 4 H), 2.29 (s, 3 H), 1.94 (s, 6 H), 1.78-1.86 (m, 4 H), 1.64-1.70 (m, 4 H), 1.44-1.52 (m, 4 H), 1.26-1.40 (m, 28 H); 13C NMR (125 MHz, CDCl3) δ167.55, 161.08, 159.47, 147.08, 146.48, 136.62, 127.52, 125.07, 124.22, 123.54, 123.36, 114.69. 110.59, 68.34, 68.29, 64.84, 29.55, 29.52, 29.39, 29.26, 28.65, 26.13, 26.04, 26.00, 18.32, 16.37.

[0037] (Experimental Example 3) (Synthesis of azo compound monomer 2) Synthesis of C16-azo(m=14) (1) Experimental Example 3-1: Synthesis of C16-azo intermediate (formula (8)) [ka] 4,4'-Dihydroxy-3-methylazobenzene (formula (5), 0.16g, 0.7mmol), 16-bromo-1-hexadecanol (0.48g, 1.5mmol, Tokyo Chemical Industry Co., Ltd.), potassium carbonate (0.69g, 5mmol, Fuji Film Wako Pure Chemical Co., Ltd.), and potassium iodide (33mg, 0.20mmol, Fuji Film Wako Pure Chemical Co., Ltd.) were added with 15ml of N,N-dimethylformamide (DMF, Fuji Film Wako Pure Chemical Co., Ltd.). This mixture was stirred at 120°C for 72 hours, and then water was added to precipitate the product. The precipitate was filtered and recrystallized from ethanol to obtain a yellow powder (8) (C16-azo intermediate, m=14).

[0038] 1H NMR (500 MHz, CDCl3) δ7.85 (d, J = 8.9, 2 H), 7.71-7.74 (m, 2 H), 6.98 (d, J = 9.0, 2 H), 6.90 (d, J = 9.3, 1 H), 4.01-4.06 (m, 4 H), 3.64 (t, J = 6.7, 4 H), 2.29 (s, 3 H), 1.78-1.86 (m, 4 H), 1.54-1.59 (m, 4 H), 1.44-1.52 (m, 4 H), 1.26-1.40 (m, 36 H); 13 C NMR (100 MHz, CDCl3) δ161.04, 159.45, 146.99, 146.37, 127.51, 124.19, 123.45, 123.38, 114.64, 110.51, 68.31, 68.25, 63.10, 32. 81, 29.66, 29.60, 29.44, 29.39, 29.25, 29.22, 26.11, 26.02, 25.74, 16.41

[0039] (2) Example 3-2: Synthesis of C16-azo intermediate (formula (9), m=14)

change

[0040] 1 H NMR (500 MHz, CDCl3) δ7.85 (d, J = 9.0, 2 H), 7.72-7.73 (m, 2 H), 6.99 (d, J = 9.0, 2 H), 6.90 (d, J = 9.3, 1 H), 6.09 (s, 2 H), 5.54 (s, 2 H), 4.14 (t, J = 6.74, 4H), 4.01-4.04 (m, 4 H), 2.29 (s, 3 H), 1.94 (s, 6 H), 1.78-1.86 (m, 4 H), 1.63-1.69 (m, 4H), 1.26-1.54 (m, 48H); 13 C NMR (125 MHz, CDCl3) δ169.39, 167.57, 147.07, 144.96, 143.21, 135.31, 128.68, 125.06, 124.21, 123.54, 123.35, 114.70,110.61, 68.37,64.86,29.67,29.59,29.53,29.40,29.27,28.65,26.14,26.05, 26.00, 18.32,16.37.

[0041] (Experimental Example 4) (Synthesis of polymer (adhesive) and preparation of its film) DGI (1) (22 mg) prepared in Experimental Example 1, azo compound (7) (6 mg (m=10)) prepared in Experimental Example 2, and 0.5 mg of 1,1'-azobis-(cyclohexane-1-carbonitrile, manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were placed in a vial and melted by heating to 70°C. 20 μL of toluene was added thereto to reduce the viscosity. This mixture was poured into a liquid crystal cell (parallel alignment, area: 2 cm × 2 cm, manufactured by EHC Co., Ltd.). This cell was heated on a hot plate at 120°C for 24 hours or more. The polymerization was carried out under conditions without illumination (dark room). After heating, it was allowed to cool to room temperature, and the film was removed from the liquid crystal cell and used. The film produced (weight ratio of azo compound to DGI (azo compound / DGI=6 / 22, weight ratio of azo compound to DGI was approximately 27%)) was 15-20 μm thick and 1.0 cm × 0.6 cm in size. This film was designated Sample 1. In addition, the weight ratio of the azo compound to DGI was changed to (azo compound / DGI) = 9 / 41 (weight ratio of the azo compound to DGI: approximately 22%), and a film with a thickness of 15-20 μm and a size of 1.5 cm × 1.5 cm was produced in the same manner as sample 1. The film was then cut into a long and narrow film of 1.5 cm × 2 mm. This film was named sample 2.

[0042] A probe tack test was also conducted using the film (sample 1) prepared by the above method. A glass ball-shaped probe was pressed against the surface of the photoresponsive film (sample 1) for 10 seconds to bring it into contact with the film, and the test force (adhesive force) was measured when peeling the film off. Figure 6 shows an explanatory diagram of the probe tack test, Figure 7 shows the results of the probe tack test (relationship between test force and test time), and Figure 8 shows the adhesion before and after UV light irradiation (room light only). In particular, the test force depends on the peel speed. The faster the peel speed in the probe tack test, the greater the test force. In this test, a probe tack tester (load displacement measuring instrument FSA-1KE-5N 81010, manufactured by Imada Co., Ltd.) was used to attach the adhesive 7 to a glass plate 11, and the tip 9a of the probe 9 was lowered (a) and pressed against the adhesive 7 for 2 seconds, and after being in contact with the film surface for 10 seconds (b), it was peeled off (c), and the test force at that time was measured. This measurement was carried out both before and during ultraviolet light irradiation. During ultraviolet light irradiation (a), a UV light 13 (HLV-24UV365, manufactured by CCS Inc.) was used to irradiate the adhesive 7 with ultraviolet light of 365 nm (80 mW / cm 2 , 50-100W / cm 2 (which may be performed by irradiation with light) was applied from below the glass plate 11 during the measurement.

[0043] In the probe tack test in Figure 7, F p indicates the force applied when pressing. t D indicates the contact time with the film surface. F ad indicates the test force when peeling. From Figure 8, it can be seen that the faster the peeling speed, the stronger the adhesive strength (bonding force). It was also confirmed that the adhesive strength changes depending on whether or not UV light is irradiated, and that UV light irradiation reduces the adhesive strength regardless of the peeling speed.

[0044] Fig. 9 shows an optical microscope (Olympus Corporation, BX-51) photograph of the film of Sample 1 when a photomask was used to expose both areas of the film irradiated with ultraviolet light and areas of the film not irradiated with ultraviolet light (Fig. 9(A)). A metal photomask was placed on the film surface, and ultraviolet light (100 mW / cm2) was applied to the film using a UV light. 2 ) for a few seconds. As soon as the UV light was removed, the sample was focused and observed under an optical microscope. The irradiated sample was also observed under a laser confocal microscope (Keyence, VK-X100 series). A laser microscope photograph of the surface shape (Figure 9(B)) and an optical microscope photograph (room light) before irradiation with UV light (Figure 9(C)) are also shown. From these photographs, it was confirmed that the film was flat before UV irradiation, but that the film underwent localized shape changes upon UV irradiation. In other words, it can be said that the target object can be easily removed due to such uneven shape changes upon UV irradiation.

[0045] (Experimental Example 5) In addition, the effective elastic modulus (Young's modulus) including viscoelasticity of the film (sample 1) was measured using a tensile testing device (EZ-LX, manufactured by Shimadzu Corporation). In the case of adhesive materials, it is common to measure the effective elastic modulus while stretching at a constant speed in order to capture the viscous effect, and measurements were made in the range of 0.001-0.17 mm / s. In addition, this measurement speed is very slow, and the elastic component is the main component in the obtained effective elastic modulus, and at the same time, it is within the range usually used for measuring the elastic modulus of such adhesive materials. The stress-strain curve of the film (not shown) was obtained before and after irradiation with ultraviolet light (room light) and after irradiation with ultraviolet light (100 mW / cm 2 ) and during irradiation (measurement while irradiating). Young's modulus (MPa) was calculated from the slope of the stress-strain curve at a strain of about 10%. [Table 1] Table 1 above shows that the effective Young's modulus of the film was decreased by irradiation with ultraviolet light. Before irradiation with ultraviolet light, the Young's modulus of the film was about 10-22 MPa, and after irradiation with ultraviolet light, it was about 8-18 MPa. It also shows that the effective Young's modulus value increases with increasing measurement speed, but even with the effect of viscoelasticity included, the effective elastic modulus is also small, that is, it can be said to be soft, so it can be said that this film is very soft compared to the film described in Non-Patent Document 1, for example.

[0046] (Experimental Example 6) Using the film (sample 1) produced by the above method, a polystyrene ball (diameter 5 mm, weight 0.2 g) was adhered and removed as a target object. In an indoor lighting environment, as shown in Figure 10, the ball was pressed against the film to adhere it, and then the glass was fixed with the ball facing downwards (Figure 10(A)). The film was left fixed to the glass as it was produced. Then, a UV light was used to illuminate the ball (365 nm, 80 mW / cm 2 ) from above, causing the ball to fall within 1-2 seconds (Figure 10(B)).

[0047] (Experimental Example 7) Using the film (sample 2) produced by the above method, the following objects were bonded to the film: polystyrene, silicon wafer, fluororubber, polypropylene, and aluminum foil. Two samples were used for polystyrene, and one sample was used for the other objects. Polystyrene: Made by Stangood Test Piece Co., Ltd., product number: STP011-1343-1, thickness 3.5 mm, diameter 3.04 mm, weight 25 mg and thickness 3.4 mm, diameter 3.20 mm, weight 26 mg Silicon wafer: FLUOROWARE, product number: H22-40, thickness: 0.54 mm, size: 13 x 7 mm, weight: 118 mg Fluororubber: Made by Masuoka Corporation, product number: p-7 O-ring, thickness 2.0 mm, diameter 11 mm, weight 15 mg Polypropylene: AS ONE Corporation, VIOLAMO (registered trademark), product number: V-200BH, thickness 1.08 mm, size: diameter 7 mm x length 51 mm, weight 282 mg Aluminum foil: Aluminum foil manufactured by UALJ Corporation, thickness 0.09 mm x 4 = 0.36 mm, size 5 mm x 60 mm, weight 130 mg

[0048] Figure 11(A) shows a photograph of only the film, Figure 11(B) shows polystyrene, Figure 11(C) shows a silicon wafer, Figure 11(D) shows fluororubber, Figure 11(E) shows polypropylene, and Figure 11(F) shows aluminum foil adhered to the film (the scale is the same for all photographs). After pressing each sample against the film to adhere it, the film was oriented vertically and the tip of the film was fixed with the clamps of the tensile tester. Note that the entire film was not fixed, only the top and bottom tips were fixed. At this time, each sample was able to maintain its state (for example, for several tens of minutes to several hours) without coming off while adhered to the film. This experimental example shows that reversible adhesion is possible without residuals to flat, spherical, and convex surfaces made of different materials, such as hard and soft. Furthermore, even with a film of this thickness and size, it is possible to adhere, transport, and detach samples of approximately 1.5 cm x 2 mm x 20 μm in size and weighing 10 mg to 300 mg.

[0049] (Experimental Example 8) FIG. 12 shows an example of the film being used underwater. Distilled water was poured into a beaker, and aluminum foil (5mm x 35mm) was pressed onto the film (sample 2) to adhere it, then tweezers were used to place it underwater (Figure 12). It was confirmed that it would not fall off when left in the water or when shaken up and down in this state. The weight of the adhered aluminum foil was approximately 50 times that of the film. If the entire film was fixed in place, it was also possible to remove the aluminum foil underwater using UV light. One method in which adhesive films can be used underwater is to transport biological samples (eg, tissue, skin, etc.).

[0050] According to this embodiment, by utilizing the rapid and reversible change in mechanical properties due to the presence or absence of ultraviolet light irradiation, the objects to be bonded can be detached, making it easy to redo the bonding and recycle the adhesive after use, which also leads to resource saving. In particular, it is possible to realize temporary fixing of semiconductor parts, electrical equipment parts, precision optical parts, etc., attachment and detachment of medical parts with low irritation, and product assembly processes with excellent reworkability. In addition, since bonding is possible under high humidity environmental conditions such as underwater, the range of applications is wide. [Industrial Applicability]

[0051] The present invention can be used as an adhesive and a manufacturing method thereof for a variety of applications, including small items such as semiconductor parts, electrical equipment parts, precision optical parts, and medical materials, as well as biological samples such as water-containing biological tissues and cells. [Explanation of symbols]

[0052] 1. DGI Monomer 3. Azo compound monomers 5 Crosslinked polymer structure 7 Adhesive material 9. Probe 11 Glass Plate 13. UV Light 15, 17 Object

Claims

1. Dodecyl glyceryl itaconate represented by the following formula (1), 【Chemistry 1】 It includes a copolymer with a photoresponsive azo compound represented by the following formula (2), 【Chemistry 2】 (In formula (2), m is selected from an integer of 10 to 14.) The adhesive strength changes depending on the presence or absence of ultraviolet light irradiation, and decreases when irradiated with ultraviolet light, and returns to its original strength when not irradiated with ultraviolet light without being irradiated with any other light.

2. The adhesive material according to claim 1 , wherein the photoresponsive azo compound is in a liquid crystal phase.

3. 3. The adhesive material according to claim 1, wherein a weight ratio of the photoresponsive azo compound to the dodecylglyceryl itaconate is 50% or less.

4. 3. The adhesive according to claim 1, wherein the elastic modulus of the adhesive is lower when irradiated with ultraviolet light than when not irradiated with ultraviolet light, and the elastic modulus changes by 8-22 MPa between when irradiated with ultraviolet light and when not irradiated with ultraviolet light.

5. The adhesive according to claim 3, wherein the elastic modulus of the adhesive is lower when irradiated with ultraviolet light than when not irradiated with ultraviolet light, and changes between 8-22 MPa when irradiated with ultraviolet light and when not irradiated with ultraviolet light.

6. The adhesive material according to claim 1 or 2, which is used underwater.

7. The adhesive material according to claim 3, which is used underwater.

8. The adhesive material according to claim 4, which is used underwater.

9. A method for producing the adhesive material according to claim 1 or 2, comprising the steps of: Dodecyl glyceryl itaconate represented by the following formula (1), 【Chemistry 3】 A photoresponsive azo compound represented by the following formula (2): 【Chemistry 4】 (In formula (2), m is selected from an integer of 10 to 14.) A method for producing an adhesive material, comprising copolymerizing

10. The method for producing an adhesive material according to claim 9 , wherein a weight ratio of the photoresponsive azo compound to the dodecylglyceryl itaconate is 50% or less.

11. A method for using the adhesive material according to claim 1 or 2, comprising: A method for using the adhesive material, comprising adhering an object to the adhesive material and storing or transporting the object.

12. A method for using the adhesive material according to claim 4, comprising the steps of: A method for using the adhesive material, comprising adhering an object to the adhesive material and storing or transporting the object.

13. A method for using the adhesive material according to claim 6, comprising the steps of: A method for using an adhesive comprising the steps of: adhering an object to the adhesive; and storing or transporting the adhesive in water.

14. A method for using the adhesive material according to claim 8, comprising: A method for using an adhesive comprising the steps of: adhering an object to the adhesive; and storing or transporting the adhesive in water.

Citation Information

Patent Citations

  • Photoresponsive azo compound, photoresponsive composition, photoresponsive polymer compound, adhesive, photoresponsive body, and method for producing photoresponsive polymer compound

    JP6938063B2

  • Photoresponsive polymer compound, adhesive, photoresponsive body, and method for producing photoresponsive polymer compound

    JP7012392B2